2018
DOI: 10.31580/ijer.v1i1.140
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Firm Performance Nexus: A Case of Cement Industry of Pakistan

Abstract: Corporate governance is the system of rules, practices and method by that business corporations are directed and controlled. The aim of this research is to examine the impact of the corporate governance on the financial performance of the enlisted cement industry on the Pakistan Stock Exchange from the year 2013-17. This research is a “quantitative research” which focuses on numbers and results based on empirical analysis of actual data and logic. Ten out of seventeen cement firms listed at PSX from the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The code of corporate governance is treated as a fundamental element, especially in developing countries. The code of corporate governance of Pakistan are determined by the Security and Exchange Commission of Pakistan (SECP) in March 2002 (Kazi, Arain, & Sahetiya, 2018). It is revealed that ownership structure is a crucial element and plays a vital role in firm performance (Shah, Xiao, & Quresh, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The code of corporate governance is treated as a fundamental element, especially in developing countries. The code of corporate governance of Pakistan are determined by the Security and Exchange Commission of Pakistan (SECP) in March 2002 (Kazi, Arain, & Sahetiya, 2018). It is revealed that ownership structure is a crucial element and plays a vital role in firm performance (Shah, Xiao, & Quresh, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A company's management, board, shareholders, and other stakeholders are said to be involved in a complex of interactions known as corporate governance [56]. The company's stakeholders, which include its owners, creditors, management, employees, customers, and the general public, can formulate and address issues as they arise through the use of corporate governance.…”
Section: Social Concernsmentioning
confidence: 99%
“…The company's stakeholders, which include its owners, creditors, management, employees, customers, and the general public, can formulate and address issues as they arise through the use of corporate governance. Additionally, it is believed that the establishment of sound corporate governance is essential for the development of a competitive market [56,57]. In reality, good capital markets are stabilized and strengthened by good corporate governance standards, and investors are protected [57].…”
Section: Social Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corporate governance is treated as a basic element in developing countries. As corporate governance code of Pakistan are determined by the Security and Exchange Commission of Pakistan (SECP) in March 2002 (Kazi, Arain, & Sahetiya, 2018) and stated that ownership structure and board characteristics are essential elements in firm performance in the corporate governance perspectives (Shah, Xiao, & Quresh, 2019). Firm ownership and management are considered primary indicators which can be helpful in controlling and monitoring effectively the plans, authority control, resource allocation and many other indicators which are useful for firm performance (Carney, 2005; Daily, Dalton, & Cannella Jr, 2003; Daspit, Chrisman, Sharma, Pearson, & Mahto, 2018).…”
Section: Introductionmentioning
confidence: 99%